WANPRESTASI YANG DILAKUKAN OLEH DEBITUR ATAS PERJANJIAN KREDIT DENGAN JAMINAN HAK TANGGUNGAN (STUDI KASUS PUTUSAN NOMOR 250/PDT.G/2020/PN.JKT.BRT) - Syahrani Mutiara Afifah (Jurnal Hukum Adigama, 2021)
A credit agreement is a bond between a creditor and a debtor whose contents determine and regulate the rights and obligations of both parties in relation to the granting of credit. The provision of bank credit facilities as creditors will require guarantees as security and certainty, because without bank guarantees it will be difficult to avoid risks that may occur if the debtor breach of contract. The guarantee that is considered the safest by the bank is the mortgage. If the guarantee is still tied to the mortgage but the certificate is broken, the mortgage will be nullified by law. Therefore, it is necessary to make a new Mortgage Deed. This thesis discusses how the breach of contract committed by the debtor on a credit agreement with a mortgage guarantee (case study of decision number 250/Pdt.G/Pn.Jkt.brt) and what are the implications of breaking a certificate that is still bound by a mortgage. In this study, the author uses a normative legal research method, where the research data studied is seen to be in accordance with the laws and regulations. The results of this study can be concluded that the factors causing the occurrence of bad loans are internal and external factors. The split of the certificate occurs due to the granting of new rights, the bank will execute the certificate that has been split to the debtor to provide a Power of Attorney to impose Mortgage and a new Deed of Granting Mortgage.